Respuesta :
Answer:
- We assume before this you have learned how to multiply two monomials and monomial with binomial.
Use the following formula to multiply binomials:
- (a + b)(c + d) = ab + ad + bc + bd
Applied to the given expression, we have:
- (x + 2)(x - 4), where a = x, b = 2, c = x , d = -4
Expand as indicated above:
- (x + 2)(x - 4) =
- x(x) + x(-4) + 2(x) + 2(-4)
Now simplify
- x² - 4x + 2x - 8
Collect like terms, (-4x) and (2x):
- x² + (-4x + 2x) - 8 =
- x² - 2x - 8
This is how you can do same order operations with any binomials.
We can simply use distributive law of grade 1
- (a+b)(c+d)=ac+ad+bc+bd
I assume you know multiplication of monomials
So
- (x+2)(x-4)
- x(x-4)+2(x-4)
- x²-4x+2x-8
- x²-2x-8